Penerapan Metode MOORA pada Sistem Pendukung Keputusan Penerimaan Crew Rahwana Wedding Organizer Berbasis Website - Hanif Hilmi Setyawan (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
A Decision Support System is a system designed with the capability to solve problems, particularly in decision-making. One example is making decisions regarding the recruitment of prospective employees or crew members for a company. In this research case study, the Decision Support System will be implemented to assist in recruiting crew members for Wedding Organizer Rahwana. A Wedding Organizer is a service-oriented business that plans and manages all aspects of a wedding event. In this case, Rahwana WO is still facing difficulties in selecting potential crew members. The implemented Decision Support System will use the MOORA method, a multi-objective optimization technique that has been successfully applied to solving various complex decision-making problems. The system’s performance was evaluated using the SUS method, and the implementation of this approach for Rahwana WO’s crew selection received a good rating, categorized as GOOD, with a score of 78.6.